Imam Bazzar’s approach to deal with difference of replacing one companion with another in the chain of narrators.: الأحاديث التي أعلها الامام البزار بالاختلاف في ابدال الصحابي بالآخر( مسند أنس بن مالك رضي الله عنه نموذجا) - Akram, Reema (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Hidden defects in a hadith are subtle flaws that can undermine a narration’s authenticity even if its chain of narrators appears sound. Misattributing a hadith and replacing one companion with another is one of the hidden defects that occur in the chain of narrators and lead to weakening of hadith. Therefore, judgement on such traditions is based on certain factors which are discussed in the sciences of hadith and its hidden defects. This paper analyzes approach of Imam Al-Bazzar in dealing with hidden defect of replacing one companion with another in the chain of narrators and its effects on judgement of Hadith.